2002
DOI: 10.1111/j.1469-8749.2002.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal Doppler assessment of cerebral blood flow velocity in healthy preterm and term infants

Abstract: The aim of the present study was to generate normal reference data for anterior and middle cerebral artery blood flow velocity and resistance index in preterm and term infants during the first 8 hours of life. The study population longitudinally included 120 healthy preterm and term infants (gestational age 24 to 41 weeks), all of appropriate weight for gestational age. The following parameters were studied: peak‐systolic velocity, end‐diastolic velocity, mean velocity, and resistance index. All parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…In 17 "healthy" normocapnic (35-50 mm Hg) ventilated infants born at 24-28 weeks' gestation, Pezzati et al [6] reported that middle cerebral artery mean CBFv during the first 2-8 hours was 10 ± 3 cm/sec, which is similar to our initial and earliest value of 10.1 (95% CI 6.8-13.3) cm/sec for [23][24] week infants, at ∼6 hours of age. "Healthy" infants were described as those without significant maternal pregnancy complications, intrauterine growth restriction, malformations, perinatal asphyxia, infection, thrombocytopenia, anemia, polycythemia, hypotension, hypertension, intraventricular hemorrhage (IVH) ≥grade 2, or hemodynamically significant patent ductus arteriosus [6]. Measurements were always performed ≥1 hour after surfactant administration [13].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In 17 "healthy" normocapnic (35-50 mm Hg) ventilated infants born at 24-28 weeks' gestation, Pezzati et al [6] reported that middle cerebral artery mean CBFv during the first 2-8 hours was 10 ± 3 cm/sec, which is similar to our initial and earliest value of 10.1 (95% CI 6.8-13.3) cm/sec for [23][24] week infants, at ∼6 hours of age. "Healthy" infants were described as those without significant maternal pregnancy complications, intrauterine growth restriction, malformations, perinatal asphyxia, infection, thrombocytopenia, anemia, polycythemia, hypotension, hypertension, intraventricular hemorrhage (IVH) ≥grade 2, or hemodynamically significant patent ductus arteriosus [6]. Measurements were always performed ≥1 hour after surfactant administration [13].…”
Section: Discussionsupporting
confidence: 79%
“…While CBFv reference values have not been previously reported for infants this immature, one study examined middle cerebral artery CBFv in relatively stable premature infants born at 24-28 weeks' [6]. In 17 "healthy" normocapnic (35-50 mm Hg) ventilated infants born at 24-28 weeks' gestation, Pezzati et al [6] reported that middle cerebral artery mean CBFv during the first 2-8 hours was 10 ± 3 cm/sec, which is similar to our initial and earliest value of 10.1 (95% CI 6.8-13.3) cm/sec for [23][24] week infants, at ∼6 hours of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether or not flow indices are good indicators to assess cerebral hemodynamics remains controversial. 11,33,35,36 In neonatology, RI has been used to predict outcome in infants with neonatal encephalopathy. A low RI (<0.55) has been associated with poor neurological outcome, 37 but this association appears weaker during therapeutic hypothermia.…”
Section: New Features Obtained With Neodopplermentioning
confidence: 99%